(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Sergienko I.V. Keywords: a consciousness stream, mythological component, epiphanies, creative heritage, interview and lectures. The article offers the interpretation of the creativity of the Irish writer as viewed by the writer Vladimir Nabokov. J. Joyce’ novel ‘Ulysses’ is placed in the center of attention. The author focuses his study on the writer’s use of his characters’ consciousness stream as well as the attempt to intertwine the elements of mythology and epiphany as a means to render hidden symbols and implications. The interest in Nabokov’s analysis of J.Joyce can also help to study the literary heritage of the former through his interviews and lectures on foreign literature.